Doctrinal studies of the constitutional human right to housing - Мойсей, Любомир Олексійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The topical problems related to housing of the military servicemen, the directions of improving and of providing observance of the housing law are considered as well as the waiting list of servicemen in Armed Forces of Ukraine is analyzed. The purpose of this paper is to study the natural law and positivist approaches to solving the human rights issues based on constitutional recognition of fundamental rights and freedoms. Relevance of the article consists in the nature and meaning of doctrinal study of the constitutional right to housing, the positive dynamics of sustainable development and establishment of human rights that has a long history which was accompanied by the struggle of doctrines and traditions specific to one or another country.